Control and automation of multilayered integrated microfluidic device fabrication. Issue 3 (19th January 2017) - Kipper, Sarit; Frolov, Ludmila; Guy, Ortal; Pellach, Michal; Glick, Yair; Malichi, Asaf; Knisbacher, Binyamin A.; Barbiro-Michaely, Efrat; Avrahami, Dorit; Yavets-Chen, Yehuda; Levanon, Erez Y.; Gerber, Doron
Abstract : A computerized semiautomatic aligner aligns multilayer devices comprising intricate microfeatures several-fold more accurately than manual alignment. Abstract : Integrated microfluidics is a sophisticated three-dimensional (multi layer) solution for high complexity serial or parallel processes. Fabrication of integrated microfluidic devices requires soft lithography and the stacking of thin-patterned PDMS layers. Precise layer alignment and bonding is crucial. There are no previously reported standards for alignment of the layers, which is mostly performed using uncontrolled processes with very low alignment success. As a result, integrated microfluidics is mostly used in academia rather than in the many potential industrial applications. We have designed and manufactured a semiautomatic Microfluidic Device Assembly System (μDAS) for full device production. μDAS comprises an electrooptic mechanical system consisting of four main parts: optical system, smart media holder (for PDMS), a micropositioning xyzθ system and a macropositioning XY mechanism. The use of the μDAS yielded valuable information regarding PDMS as the material for device fabrication, revealed previously unidentified errors, and enabled optimization of a robust fabrication process. In addition, we have demonstrated the utilization of the μDAS technology for fabrication of a complex 3 layered device with over 12 000 micromechanical valves and an array of 64 × 64 DNA spots on a glass substrate with high yield and high accuracy. We increased fabrication yield from 25% to about 85% with an average layer alignment error of just ∼4 μm. It also increased our protein expression yields from 80% to over 90%, allowing us to investigate more proteins per experiment. The μDAS has great potential to become a valuable tool for both advancing integrated microfluidics in academia and producing and applying microfluidic devices in the industry.